Immunotherapy of pancreatic cancer - weal and woe - Bazhin, Alexandr V.; Werner, Jens; Karakhanova, Svetlana (Translational cancer research, 2016)
We appreciated reading the commentary “Pancreatic ductal adenocarcinoma—a new hope?” of Irving and Lobo (1) on our recent paper in the British Journal of Cancer (2). Indeed, pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers in the world. At present, only multimodal treatment including surgical resection can prolong survival of patients with this disease (3). Therefore, new therapeutic approaches against PDAC are urgently needed. One new option is to apply immunotherapy for these patients. Immunotherapy possesses a bright spectrum of approaches: (I) passive immunotherapy includes a treatment of patients with monoclonal antibodies (specific immunotherapy) or checkpoint inhibitors (non-specific immunotherapy); (II) cancer vaccines and cellular therapy belong to the active immunotherapy as well as interferon treatment (non-specific immunotherapy).
Gesehen am 04.05.2020